If the first two numbers of a sequence are 1 & 3 and the sum of n th number and ( n − 1 ) th number is the next number,then it will be "Fahim's sequence." The first few numbers of Fahim's sequence are: 1 , 3 , 4 , 7 , . . . . If you divide the n th number of this sequence by a constant,then you will get close to the n th number of the Fibonacci sequence. What is the constant?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
In general, a sequence { a n } n ∈ N defined by
a n = ⎩ ⎪ ⎨ ⎪ ⎧ a b a n − 1 + a n − 2 for n = 1 for n = 2 else
can be calculated by the explicit formula
a n = c 1 ϕ n + c 2 ϕ n
where ϕ and ϕ are the golden ratio and its conjugate respectively.
The constants c 1 and c 2 depend on the starting values a and b . We can set up two equations and solve for c 1 and c 2 .
a = a 1 b = a 2 = c 1 ϕ + c 2 ϕ = c 1 ϕ 2 + c 2 ϕ 2
c 1 = ϕ + 2 − a 1 + a 1 ϕ + a 2 c 2 = 1 − 2 ϕ a 1 + a 1 ϕ − a 2 ϕ
With this, we can now also solve for the general ratio r of two such sequences f n = c 1 ϕ n + c 2 ϕ n and g n = c 3 ϕ n + c 4 ϕ n .
r = n → ∞ lim f n g n = n → ∞ lim c 1 ϕ n + c 2 ϕ n c 3 ϕ n + c 4 ϕ n = n → ∞ lim c 1 + c 2 ( ϕ ϕ ) n c 3 + c 4 ( ϕ ϕ ) n = c 1 c 3 = 2 f 2 − f 1 + f 1 5 2 g 2 − g 1 + g 1 5 ∣ ∣ ϕ / ϕ ∣ ∣ < 1
In our specific case, we have f 1 = 1 ; f 2 = 1 ; g 1 = 1 ; g 2 = 3 which results in
r = 1 + 5 5 + 5 = 5
= = 1 + 5 5 + 5 5 + 1 5 ⋅ ( 5 + 1 ) 5
Problem Loading...
Note Loading...
Set Loading...
Let ρ be the golden ratio , and ρ = 1 − ρ be its conjugate. Indexing the Fibonacci sequence so that F 1 = F 2 = 1 , the Binet formula says that F n = 5 1 ( ρ n − ρ n ) . Call Fahim's sequence G n ; then the same methods as Binet's formula lead to the formula G n = ρ n + ρ n . (You can prove this by induction, even if you don't see how to derive it.)
So n → ∞ lim F n G n = 5 n → ∞ lim ρ n − ρ n ρ n + ρ n = 5 n → ∞ lim 1 − ( ρ / ρ ) n 1 + ( ρ / ρ ) n = 5 , since ∣ ρ / ρ ∣ < 1 .